Ecoladrillos: An alternative for the Use of Recycled Clay and Rubber Grain (2023)
The excessive population growth accompanied by the variety of economic activities that humanity carries out to obtain sustenance are triggering an increase in the consumption of natural resources and in the production of waste, with the consequent environmental impact. This reality has motivated looking for alternatives to incorporate certain waste into the production chain in order to reduce overconsumption of raw materials in certain construction materials. For this reason, for example, there are options to use raw material recovered from tires in asphalt mixes, mortar, and concrete, among others. This study demonstrates the technical, environmental and economic viability of eco-bricks of soil-cement and soil-cement-grain plastic GCR. Masonry was made of 70% previously sieved clay with 20% cement and 10% sand, adding the necessary water for workability. Also, clay-cement and recycled rubber (GCR) specimens were prepared using 7% of rubber that was the addition that favored the mechanical behavior of the prepared brick. The general analysis of the technical, environmental and economic results obtained allows us to affirm that these eco-bricks contribute to the disposal of waste.  JEL Codes: R31 Received: 03/03/2023.  Accepted: 01/05/2023.  Published: 14/06/2023.